SUNLIT AND SHADED MAIZE CANOPY WATER LOSS UNDER VARIED WATER STRESS - Antonio Odair Santos; Homero Bergamaschi; Marcel Fuchs; Luís Mauro G. Rosa; João Ito Bergonci (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The precise estimation of transpiration from plant canopies is important for the monitoring of crop water use and management of many agricultural operations related to water use planning. The aim of this study was to estimate transpiration from sunlit and shaded fractions of a maize ( Zea mays L.) canopy, using the Penman-Monteith energy balance equation with modifications introduced by Fuchs et al. (1987) and Fuchs & Cohen (1989). Estimated values were validated by a heat pulse system, which was used to measure stem sap flow and by a weighing lysimeter. A relationship between incident radiation and leaf stomatal conductance for critical levels of leaf water potential was used to estimate transpiration. Results showed that computed transpiration of the shaded canopy ranged from 27 to 45% of the total transpiration when fluctuations in atmospheric demand and the level of water stress were taken in account. Hourly and daily estimates of transpiration showed agreement with lysimeter and heat pulse measurements on the well-watered plots. For the water-limited plots the precision of the estimate decreased due to difficulties in simulating the canopy stomatal conductance.